Najah Al-Qari Sharh Sahih Al-Bukhari (d. 256 AH) Youssef Effendi Zadeh (d.1167 AH) The Book of Literature is a Section on Good Manners, Generosity And Miserliness (Islamic Sciences Journal, 2023)
ABSTRACT               If we look at this research we will notice that the characteristics of a human being by which he treats others,are commendable and reprehensible. For what is commendable on the whole: that you should be with others on yourself and do justice to them and do not do justice to yours. And what is reprehensible against it, and good manners of all kinds is divided into two parts:The first section: Instinct.The second section: acquired.That is why it is clear to us through this research that creation is a splendor in the type of a human being, who are among the characteristics of the prophets, and the cycle of virtues at which they are different.
Keywords: Islamic Sciences, Continental Success, Hadith, Najah Al-Qari And Generosity.